2015
DOI: 10.18203/2349-2902.isj20150682
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidence and the value of SOFA and MOD scoring in predicting the outcome in acute mesenteric ischemia

Abstract: Background: Acute mesenteric ischemia (AMI) is defined as a sudden loss of blood supply to visceral tissue, and it potentially results in intestinal infarction. AMI is an uncommon (1-2 per 1000 hospital admissions) but highly complex clinical problem. Mortality from AMI remains high despite an aggressive approach consisting of early diagnosis, restoration of arterial perfusion, resection of nonviable intestine, second-look laparotomy, and supportive intensive care with an average from published reports ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
2
0
2
Order By: Relevance
“…[8] Viswanathan et al [19] have reported higher SOFA scores both in survivors and non-survivors compared to our study (3 vs 8.82; 8 vs 12.86, respectively). [19] Even though the scores of all 3 systems were different in the survival groups, the predicted mortality rates using the SAPS II were more accurate than those using the APACHE II and SOFA scoring systems. Among patients with predicted mortality < 10%, SAPS II was the scoring system closer to the predicted mortality, whereas APACHE II and SOFA overestimated mortality.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…[8] Viswanathan et al [19] have reported higher SOFA scores both in survivors and non-survivors compared to our study (3 vs 8.82; 8 vs 12.86, respectively). [19] Even though the scores of all 3 systems were different in the survival groups, the predicted mortality rates using the SAPS II were more accurate than those using the APACHE II and SOFA scoring systems. Among patients with predicted mortality < 10%, SAPS II was the scoring system closer to the predicted mortality, whereas APACHE II and SOFA overestimated mortality.…”
Section: Discussioncontrasting
confidence: 54%
“…On the other hand, the median SAPS II scores were lower than those reported by Piton et al [8] have reported in the NUTRIREA2 trial (39 vs 59). [8] Viswanathan et al [19] have reported higher SOFA scores both in survivors and non-survivors compared to our study (3 vs 8.82; 8 vs 12.86, respectively). [19] Even though the scores of all 3 systems were different in the survival groups, the predicted mortality rates using the SAPS II were more accurate than those using the APACHE II and SOFA scoring systems.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations